1997
DOI: 10.1002/hep.510250224
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a swelling-activated anion conductance in homozygous typing cell hepatoma cells

Abstract: Liver cell volume and intracellular ion concentrations are maintained within a narrow physiologic range by regulated changes in membrane ion permeability. These studies of homozygous HTC hepatoma cells, a model liver cell line, evaluate the relationship between cell volume and membrane ion permeability, and assess the possibility that cell swelling allows the efflux of the intracellular osmolite taurine through the opening of a conductive pathway. Cell swelling induced by exposure to hypotonic solutions (203 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Shortly after osmotic reduction of the bath solution, Huh‐7 cells developed, over several minutes, large outwardly rectifying currents that reversed close to the equilibrium potential for Cl ‐ , often demonstrated some degree of time‐dependent inactivation above +60 mV and were blocked by known inhibitors of VRACs including NPPB and tamoxifen. These data are consistent with similar observations made in previous whole‐cell patch‐clamp studies in a range of hepatocyte and hepatoma cells (Jackson et al ., 1996; Meng and Weinman, 1996; Bodily et al ., 1997; Feranchak et al ., 2000; Wondergem et al ., 2001) and in other cell types (Nilius et al ., 1997) and, suggest VRACs underlie the hypotonically activated currents in Huh‐7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after osmotic reduction of the bath solution, Huh‐7 cells developed, over several minutes, large outwardly rectifying currents that reversed close to the equilibrium potential for Cl ‐ , often demonstrated some degree of time‐dependent inactivation above +60 mV and were blocked by known inhibitors of VRACs including NPPB and tamoxifen. These data are consistent with similar observations made in previous whole‐cell patch‐clamp studies in a range of hepatocyte and hepatoma cells (Jackson et al ., 1996; Meng and Weinman, 1996; Bodily et al ., 1997; Feranchak et al ., 2000; Wondergem et al ., 2001) and in other cell types (Nilius et al ., 1997) and, suggest VRACs underlie the hypotonically activated currents in Huh‐7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were performed in rat ( Rattus norvegicus ) and mouse (C57BL/J6 JAX, Jackson Laboratory, Bar Harbor, Maine) liver cells and in rat hepatoma tissue culture (HTC) and human Huh7 cells, model hepatoma cell lines that express ion channels and signaling pathways similar to those found in primary rat hepatocytes 13–15. Cells were maintained in HCO 3 − ‐containing minimal essential medium (Gibco BRL, Grand Island, NY) supplemented with 10% heat‐inactivated fetal bovine serum, L ‐glutamine (2 mM), penicillin (100 IU/mL), and streptomycin (100 μg/mL), as previously described 16. Whole liver samples from obesity spontaneous mutation (ob −/− ), carbohydrate response element binding protein–deficient (ChREBP −/− ), and ob −/− + ChREBP −/− mice were provided by Dr. Kosaku Uyeda of the University of Texas Southwestern Medical Center.…”
Section: Methodsmentioning
confidence: 99%
“…Recordings were made with an Axopatch ID amplifier (Axon Instruments, Foster City, CA) and were analyzed with pCLAMP version 6.0 (Axon Instruments) 32, 33. Results are compared with control studies measured on the same day to minimize any effects of day‐to‐day variability and reported as the current density (pA/pF) to normalize for differences in cell size 16…”
Section: Methodsmentioning
confidence: 99%
“…All experiments were performed in HTC cells, a model liver cell line derived from rat hepatoma. HTC cells were obtained from Dr. Steven Lidafsky (University of Vermont) These cells have been used widely as a model of hepatocyte membrane Cl − transport because they have Cl − channels and signalling pathways analogous to those found in primary hepatocytes (Bodily et al 1997; Roman & Fitz, 1999). Cells were plated on coverslips and maintained at 37°C in a 5% CO 2 and 95% air atmosphere in culture medium containing Dulbecco's modified Eagle's medium (DMEM, Life Technologies, Inc.) supplemented with 10% fetal calf serum, 2 m m l ‐glutamine, 100 IU ml −1 penicillin and 100 μg ml −1 streptomycin.…”
Section: Methodsmentioning
confidence: 99%